Collaborative Effort Towards a FAIR and OPEN Indo-Pacific Pollen Database (IPPD) - Annika V. Herbert; Simon G. Haberle; Henry Munack; Alexandru T. Codilean (Data Science Journal)
The Indo-Pacific Pollen Database (IPPD) is a collection of modern and fossil Australian, Southeast Asian, and Oceanian pollen assemblages collected from Quaternary period depositional contexts. This compilation has been in the making since the late 1980s and is now being made available as a constituent database of Neotoma, thereby providing much needed palaeo-data coverage of the previously often underrepresented Indo-Pacific region. In addition, the IPPD is also being hosted by the OCTOPUS database, which integrates archaeology, sedimentology, geomorphology, charcoal, and non-human vertebrate fossil collections in a thoroughly Australasian context. These collections are all available in the same flattened table format, thereby providing regional researchers with multiple data types in an easily accessible manner. This will enable new avenues of cross-disciplinary research in the region. Here, we explore the collaborative efforts involved in compiling the IPPD and integrating it into OCTOPUS, as well as provide background information on both. Further, we consider future opportunities and the importance of FAIR, CARE, and OPEN data integration.